Detection of brake wear aerosols by aerosol time-of-flight mass spectrometry. (March 2016) - Beddows, D.C.S.; Dall'Osto, M.; Olatunbosun, O.A.; Harrison, Roy M.
Abstract: Brake dust particles were characterised using an Aerosol Time-of-Flight Mass Spectrometer (ATOFMS) operated using two inlet configurations, namely the aerodynamic lens (AFL) inlet and countersunk nozzle inlet. Laboratory studies show that dust particles are characterised by mass spectra containing ions deriving from Fe and Ba and although highly correlated to each other, the Fe and Ba signals were mostly detected using the nozzle inlet with relatively high laser desorption energies. When using the AFL, only [ 56 Fe] and [ −88 FeO2 ] ions were observed in brake dust spectra generated using lower laser desorption pulse energies, and only above 0.75 mJ was the [ 138 Ba] ion detected. When used with the preferred nozzle inlet configuration, the [ −88 FeO2 ] peak was considered to be the more reliable tracer peak, because it is not present in other types of dust (mineral, tyre, Saharan etc). As shown by the comparison with ambient data from a number of locations, the aerodynamic lens is not as efficient in detecting brake wear particles, with less than 1% of sampled particles attributed to brake wear. Five field campaigns within Birmingham (background, roadside (3) and road tunnel) used the nozzle inlet and showed that dust particles (crustal and road) accounted for between 3.1 and 65.9% of the particles detected, with the remaining particles being made up from varying percentages of other constituents. Highlights: Brake wear particles are an important constituent of urban aerosol. ATOFMS identifies brake dust from Fe and Ba signals. High laser pulse energies are needed to detect the Ba + ion. Data from several field campaigns are presented.